A new combination of conditional environmental distributions. (April 2018) - Horn, Jan-Tore; Bitner-Gregersen, Elzbieta; Krokstad, Jørgen R.; Leira, Bernt J.; Amdahl, Jørgen
Highlights: A joint distribution for environmental parameters including continuous directional descriptions is proposed. A folded von Mises distribution models the wind speed dependent wind direction. The model is fitted to hindcast data from a location in the central North Sea, showing good agreement. The environmental model is suitable for long-term probabilistic design of offshore wind turbines and other stationary structures. Abstract: In this paper, a joint distribution of all relevant environmental parameters used in design of offshore structures including directional components is presented, along with a novel procedure for dependency modelling between wind and wind sea. Probabilistic directional models are rarely used for response calculation and reliability assessments of stationary offshore structures. However, very few locations have the same environment from all compass directions in combination with a rotationally symmetric structure. The scope of this work is to present a general environmental joint distribution with directional descriptions for long term design of stationary offshore structures such as offshore wind turbines. Wind, wind sea and swell parameters will be investigated for a chosen location in the central North Sea.